Aurora: A non-Fickian (and Fickian) particle tracking package for modeling groundwater contaminant transport with MODFLOW. (December 2020) - Hansen, Scott K.; Berkowitz, Brian
Abstract: We introduce the Aurora software, which performs continuous time random walk (CTRW) particle tracking (PT) of dissolved contaminants on macroscopic groundwater flow fields computed using MODFLOW. This is a natural and practical approach to modeling transport at field scale: deterministic, explicitly resolved flow information is used directly while unresolved small-scale physical and chemical heterogeneity that may cause non-Fickian transport is captured by the CTRW. Existing particle trackers are limited to streamline tracing or to homogeneous velocity fields, and no existing software handles subsurface non-Fickian transport, so this represents a substantial technical advance. Fickian transport simulation can also benefit from Aurora's PT approach, which lacks numerical dispersion and other artifacts. We outline the equations Aurora implements and explain the technical and practical details of MODFLOW interoperation. Two demonstrations are presented of PT simulations using Aurora to model physics that would otherwise be difficult to treat analytically or numerically. Highlights: Aurora is the first full-physics particle tracker for groundwater transport problems. Aurora is the first software to model general non-Fickian subsurface transport. Aurora debuts a hybrid, large-scale deterministic/small-scale stochastic approach. Aurora partners with MODFLOW to obtain large-scale groundwater flow information. Aurora does (non-)Fickian particle tracking on any model MODFLOW-2005 can simulate.